Remote sensing for Antarctic geological mapping: Evidence, validation challenges and future directions - Khurram Riaz; Amin Beiranvand Pour; Aidy M. Muslim; Saima Khurram; Adel Shirazy; Aref Shirazi; Jabar Habashi; Basem Zoheir; Mazlan Hashim; Sareh Sadigh (Remote Sensing Applications: Society and Environment, 2026)

Revealing critical mineralogical insights in extreme environments using deep learning technique on hyperspectral PRISMA satellite imagery: Dry Valleys, South Victoria Land, Antarctica - Jabar Habashi; Amin Beiranvand Pour; Aidy M. Muslim; Ali Moradi Afrapoli; Jong Kuk Hong; Yongcheol Park; Alireza Almasi; Laura Crispini; Mazlan Hashim; Milad Bagheri (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Transformation in the sea surface properties of the Bay of Bengal under climate change - Mahiuddin Alamgir; Mazlan Hashim; Amin Beiranvand Pour; Shamsuddin Shahid (Ocean Dynamics, 2025)

Recurrent-spectral convolutional neural networks (RecSpecCNN) architecture for hyperspectral lithological classification optimization - Soufiane Hajaj; Abderrazak El Harti; Amin Beiranvand Pour; Younes Khandouch; Naima Benaouiss; Mazlan Hashim; Jabar Habashi; Alireza Almasi (Earth Science Informatics, 2025)

A review on hyperspectral imagery application for lithological mapping and mineral prospecting: Machine learning techniques and future prospects - Soufiane Hajaj; Abderrazak El Harti; Amin Beiranvand Pour; Amine Jellouli; Zakaria Adiri; Mazlan Hashim (Remote Sensing Applications: Society and Environment, 2024)

Recent advancement on estimation of blue carbon biomass using satellite-based approach - Dalhatu Aliyu Sani; Mazlan Hashim; Mohammad Shawkat Hossain (International Journal of Remote Sensing, 2019)

Assessment of the impact of coastal reclamation activities on seagrass meadows in Sungai Pulai estuary, Malaysia, using Landsat data (1994–2017) - Mohammad S. Hossain; Mazlan Hashim; Japar S. Bujang; Muta H. Zakaria; Aidy M. Muslim (International Journal of Remote Sensing, 2019)

Geospatial modelling of urban growth for sustainable development in the Niger Delta Region, Nigeria - Sulaiman Ibrahim Musa; Mazlan Hashim; Mohd Nadzri Md Reba (International Journal of Remote Sensing, 2019)

Landslide Mapping and Assessment by Integrating Landsat-8, PALSAR-2 and GIS Techniques: A Case Study from Kelantan State, Peninsular Malaysia - Mazlan Hashim; Syarifuddin Misbari; Amin Beiranvand Pour (Journal of the Indian Society of Remote Sensing, 2018)

Gondwana-Derived Terranes Structural Mapping Using PALSAR Remote Sensing Data - Amin Beiranvand Pour; Mazlan Hashim; Yongcheol Park (Journal of the Indian Society of Remote Sensing, 2018)

Unravelling proximate cues of mass flowering in the tropical forests of South‐East Asia from gene expression analyses - Suat Hui Yeoh; Akiko Satake; Shinya Numata; Tomoaki Ichie; Soon Leong Lee; Norlia Basherudin; Norwati Muhammad; Toshiaki Kondo; Tatsuya Otani; Mazlan Hashim; Naoki Tani (Molecular Ecology, 2017)
Elucidating the physiological mechanisms of the irregular yet concerted flowering rhythm of mass flowering tree species in the tropics requires long‐term monitoring of flowering phenology, exogenous and endogenous environmental factors, as well as identifying interactions and dependencies among these factors. To investigate the proximate factors for floral initiation of mast seeding trees in the tropics, we monitored the expression dynamics of two key flowering genes, meteorological conditions and endogenous resources over two flowering events of Shorea curtisii and Shorea leprosula in the Malay Peninsula. Comparisons of expression dynamics of genes studied indicated functional conservation of FLOWERING LOCUS T ( FT ) and LEAFY ( LFY ) in Shorea . The genes were highly expressed at least 1 month before anthesis for both species. A mathematical model considering the synergistic effect of cool temperature and drought on activation of the flowering gene was successful in predicting the observed gene expression patterns. Requirement of both cool temperature and drought for floral transition suggested by the model implies that flowering phenologies of these species are sensitive to climate change. Our molecular phenology approach in the tropics sheds light on the conserved role of flowering genes in plants inhabiting different climate zones and can be widely applied to dissect the flowering processes in other plant species.

How effective is the new generation of GPM satellite precipitation in characterizing the rainfall variability over Malaysia? - Mohd Rizaludin Mahmud; Mazlan Hashim; Mohd Nadzri Mohd Reba (Asia-Pacific Journal of Atmospheric Sciences, 2017)

Improved performance of compressed oil palm trunk prepared from modified pre-steaming technique - Nurjannah Salim; Rokiah Hashim; Othman Sulaiman; Mazlan Ibrahim; Mohammed Nasir; Masatoshi Sato; Tomoko Sugimoto; Salim Hiziroglu (Journal of the Indian Academy of Wood Science, 2016)

Comparative analysis of product-level fusion, support vector machine, and artificial neural network approaches for land cover mapping - Sharifeh Hazini; Mazlan Hashim (Arabian Journal of Geosciences, 2015)

Evaluation of Earth Observing-1 (EO1) Data for Lithological and Hydrothermal Alteration Mapping: A Case Study from Urumieh-Dokhtar Volcanic Belt, SE Iran - Amin Beiranvand Pour; Mazlan Hashim (Journal of the Indian Society of Remote Sensing, 2015)

Assessment of the impact of Landsat 7 Scan Line Corrector data gaps on Sungai Pulai Estuary seagrass mapping - Mohammad Shawkat Hossain; Japar Sidik Bujang; Muta Harah Zakaria; Mazlan Hashim (Applied Geomatics, 2015)

Mesoscale surface circulation and variability of Southern Indian Ocean derived by combining satellite altimetry and drifter observations - N. Peter Benny; Ranjan Shenbakavalli; Hashim Mazlan; Nadzri Reba Mohd; Razali Mahmud Mohd (Acta Oceanologica Sinica, 2015)

Spatial and temporal variations in the light environment in a primary and selectively logged forest long after logging in Peninsular Malaysia - Toshihiro Yamada; Aiko Yoshioka; Mazlan Hashim; Naishen Liang; Toshinori Okuda (Trees, 2014)

Comparison of ETM+ and MODIS Data for Tropical Forest Degradation Monitoring in the Peninsular Malaysia - Mazlan Hashim; Amin Beiranvand Pour; Chong Khen Wei (Journal of the Indian Society of Remote Sensing, 2014)

Exploration of gold mineralization in a tropical region using Earth Observing-1 (EO1) and JERS-1 SAR data: a case study from Bau gold field, Sarawak, Malaysia - Amin Beiranvand Pour; Mazlan Hashim; Maged Marghany (Arabian Journal of Geosciences, 2014)

Detection of chromite bearing mineralized zones in Abdasht ophiolite complex using ASTER and ETM+ remote sensing data - Mohsen Pournamdari; Mazlan Hashim (Arabian Journal of Geosciences, 2014)

Geometric and radiometric evaluation of Razaksat medium-sized aperture camera data - Mazlan Hashim; Mohamed S. El-Mahallawy; Mohd Nadzri Md Reba; Aisya Azizah Abas; Samsudin Ahmad; Xen Quan Yap; Maged Marghany; Ahmad Sabirin Arshad (International Journal of Remote Sensing, 2013)